Faktor-Faktor yang Mempengaruhi Minat Mahasiswa terhadap Kewirausahaan pada Program Studi Kimia dan Pendidikan Kimia di Universitas Papua - Ramlah, Ramlah; Murtihapsari, Murtihapsari; Lestari, Agnes Dyah Novitasari (JURNAL PENDIDIKAN DAN KEWIRAUSAHAAN, 2024)
An analysis of the factors influencing student interest in the Chemistry Study Program and the Chemistry Education Study Program on entrepreneurship in the field of chemistry has been carried out. The population investigated were active students and alumni of the two study programs at the University of Papua, Manokwari class 2013-2021. This research was carried out by analyzing data from questionnaires with a sample size of 139 people in a quantitative descriptive manner, which was carried out in September 2021. The results of the research show that the factors that influence the interest of students in the two study programs towards entrepreneurship in the field of chemistry are personality and study environment with the influence values ​​are 45.3% and 23.8% respectively. The family and social environment have an influence, but it is very small. Therefore, the study program curriculum needs to be structured in such a way as to encourage students' entrepreneurial interest in the field of chemistry.